About Linguistic Introspection as a Method of Scientific Research (Self-Observation Experience) - Palatovska, Olena (Respectus Philologicus, 2015)
The article considers introspection as a subject and method of the current linguistic research. The author of the article has undertaken an attempt to describe the introspective analysis of her own conscience directed to comprehension of the aims, problems and methods of scientific research at their initial stage. The background of this description was the newest research in the sphere of psycholinguistics, cognitive science, and discourse analysis. Algorithm of occurrence of scientific interest to a certain linguistic problem, as well as of development of its own theoretical research, comprises the following stages: observation of a certain lingual material, introspective analysis of personal reflections with the aim of constructing the research hypothesis, experimental checkup of relevance of the given hypothesis by way of referring to consciousness of other native speakers.
Keywords: introspection; observation; experimental checkup; regimes on-line and off-line; levels of consciousness